KESALAHAN UMUM DALAM TATA RIAS WAJAH DAN CARA MENGATASINYA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Background: Makeup has become an integral part of the daily routine of many individuals, especially women, as a form of self-expression and an effort to increase self-confidence. However, behind this goal, various mistakes in makeup practices still often occur and have an impact on skin health and makeup aesthetics. Objective: This study aims to identify common mistakes in makeup, analyze the causal factors, and formulate evidence-based solutions to overcome them. Method: This study uses a literature study method with a qualitative approach. Data were collected from various scientific sources including indexed journals, dermatology publications, and health articles published between 2018-2025. Data analysis was carried out using thematic synthesis techniques to group mistakes into specific categories. Results: Identification of common mistakes in makeup includes: (1) mistakes in skin preparation (skipping moisturizer, ignoring SPF protection); (2) mistakes in product selection (ignoring skin type, using expired products); (3) mistakes in application techniques (foundation color mismatch, poor blending techniques, excessive product use); (4) mistakes in tool hygiene (rarely cleaning brushes, sharing makeup tools); (5) behavioral errors (sleeping without removing makeup, being influenced by unverified social media trends). Data shows that 45.2% of makeup users have experienced skin irritation, and 56% share makeup with others. Conclusion: Makeup mistakes not only affect aesthetic results but also have the potential to damage long-term skin health. Comprehensive education on safe and skin-type-appropriate makeup practices is essential to minimize the risk of side effects. Keywords: Makeup, common mistakes, makeup techniques, skin health, cosmetic dermatology